Youths unemployment and increasing social vices in Nigeria: Entrepreneurship as a panacea (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Youths are the most active segment of the population and the key players and driver of the economy. The paper looks at youth as a group of people between the ages of 18-35 years. African youths and Nigeria in particular have been hated with the growing rate of unemployment. Some of the social vices perpetuated by the youths include armed robbery, kidnapping, prostitution, gambling, shop looting, vandalism, violent protest amongst others. The growing rate of youth’s unemployment in Nigerian has been a bane to socio-economic development of the country. The paper adopts Structural Strain Theory as a framework to the study. The theory is apt to the paper because the growing rate of youth’s unemployment is a structural and systemic issue that needs structural review. Therefore, the paper recommends skill acquisition as a panacea to curbing the growing rate of youth’s unemployment. The paper recommend further that youths should take a skill in the area of Welding and fabrication, engineering craft practice, Block laying, brick laying and concrete work, Painting and decorating, Plumbing and pipe lifting, Machine wood working, Carpentry and joinery, Furniture making, these will make the youths self-employed and self-sufficient.
Keywords: Youths; unemployment; social vices; entrepreneurship and panacea